Oral decontamination with colistin plus neomycin in solid organ transplant recipients colonized by multidrug-resistant Enterobacterales: a multicentre, randomized, controlled, open-label, parallel-group clinical trial. (June 2021) - Fariñas, Maria Carmen; González-Rico, Claudia; Fernández-Martínez, Marta; Fortún, Jesús; Escudero-Sanchez, Rosa; Moreno, Asunción; Bodro, Marta; Muñoz, Patricia; Valerio, Maricela; Montejo, Miguel; Nieto, Javier; Ruiz-San Millan, Juan Carlos; et al.
Abstract: Objectives: To evaluate the efficacy of oral colistin-neomycin in preventing multidrug-resistant Enterobacterales (MDR-E) infections in solid organ transplant (SOT) recipients. Methods: Multicentre, open-label, parallel-group, controlled trial with balanced (1:1) randomization in five transplant units. SOT recipients were screened for MDR-E intestinal colonization (extended-spectrum β-lactamase or carbapenemase producing) before transplantation and +7 and + 14 days after transplantation and assigned 1:1 to receive treatment with colistin sulfate plus neomycin sulfate for 14 days (decolonization treatment (DT) group) or no treatment (no decolonization treatment (NDT) group). The primary outcome was diagnosis of an MDR-E infection. Safety outcomes were appearance of adverse effects, mainly diarrhoea, rash, nausea and vomiting. Patients were monitored weekly until 30 days after treatment. Intention-to-treat analysis was performed. Results: MDR-E rectal colonization was assessed in 768 SOT recipients; 105 colonized patients were included in the clinical trial, 53 receiving DT and 52 NDT. No significant decrease in the risk of infection by MDR-E was observed in the DT group (9.4%, 5/53) compared to the NDT group (13.5%, 7/52) (relative risk 0.70; 95% confidence interval 0.24–2.08; p 0.517). Four patients (5.6%), three (5.6%) in the DT group and one (1.9%) in the NDT group, developed colistin resistance. Twelve patients (22.7%) in the DT group had diarrhoea, eight related to treatment (15.0%); one patient (1.8%) developed skin rash and another (1.8%) nausea and vomiting. Two patients (3.8%) in the NDT group developed diarrhoea. Conclusions: DT does not reduce MDR-E infections in SOT. Colistin resistance and adverse effects such as diarrhoea are a potential issue that must be taken seriously.